Characterization of manganese-bearing particles in the vicinities of a manganese alloy plant. (May 2017) - Hernández-Pellón, Ana; Fernández-Olmo, Ignacio; Ledoux, Frédéric; Courcot, Lucie; Courcot, Dominique
Abstract: Numerous studies have associated air manganese (Mn) exposure with negative health effects, primarily neurotoxic disorders. Despite there is not a specific European regulation, institutions such as the World Health Organization (WHO) have proposed an annual average guideline value of 150 ng/m 3 . Bioaccessibility and toxicity mechanisms of Mn remain unclear, however it is generally agreed that adverse health effects are strongly linked to particle size and morphology, chemical composition and oxidation state. This study aims to deepen the understanding of the physico-chemical characteristics of PM10 and deposition samples collected in an urban area in the proximities of a ferromanganese alloy plant. Total Mn content was determined by ICP-MS after a microwave-assisted acid digestion. The size, morphology and chemical composition of individual particles were studied by SEM-EDX. XRD was used to identify the major crystalline phases. Most of the particles observed by SEM-EDX contain Mn. 60% of Mn-PM10 particles were spheres of small size and were attributed to condensation processes at the smelting unit. Mn-bearing particles present in deposition were characterized by irregular shapes and bigger sizes, most of them consisting of SiMn slags and Mn ores and alloys, and attributed to diffuse emissions from raw material and product handling and processing. Due to the differences in the characteristics of Mn-bearing particles found in the different matrices, further studies on the potential toxicity and health effects of these particles should be done, especially in relation with the small and spherical particles present in PM10, which are expected to be more problematic. Highlights: Most of the particles collected in an urban area near a Mn alloy plant contain Mn. PM10 is mainly composed of Si-Mn particles with spherical shapes and small sizes. Mn-bearing particles in deposition samples are mostly attributed to alloys and slags. Mn solubility is expected to be higher in PM10 compared to deposition samples.